If the mean of 5 observation are x, x.2, x.4, x.6, x.8 is 11. Find the mean of first 3 observation
Answers
Answered by
2
here you go ☆☆
we know that,
▪![mean = \frac{total \: sum \: of \: observations}{total \: observations} mean = \frac{total \: sum \: of \: observations}{total \: observations}](https://tex.z-dn.net/?f=mean+%3D+%5Cfrac%7Btotal+%5C%3A+sum+%5C%3A+of+%5C%3A+observations%7D%7Btotal+%5C%3A+observations%7D+)
▪![11 = \frac{x + 2 + x + 4 + x + 6 + x + 8 + x}{5} 11 = \frac{x + 2 + x + 4 + x + 6 + x + 8 + x}{5}](https://tex.z-dn.net/?f=11+%3D+%5Cfrac%7Bx+%2B+2+%2B+x+%2B+4+%2B+x+%2B+6+%2B+x+%2B+8+%2B+x%7D%7B5%7D+)
▪![55 = 5x + 20 55 = 5x + 20](https://tex.z-dn.net/?f=55+%3D+5x+%2B+20)
▪![55 - 20 = 5x 55 - 20 = 5x](https://tex.z-dn.net/?f=55+-+20+%3D+5x)
▪![5x =3 5 5x =3 5](https://tex.z-dn.net/?f=5x+%3D3+5)
▪![x = 7 x = 7](https://tex.z-dn.net/?f=x+%3D+7)
so,
▪![<u>first observation = 7 <u>first observation = 7](https://tex.z-dn.net/?f=+%26lt%3Bu%26gt%3Bfirst+observation+%3D+7)
▪![<u> second observtion = 9 <u> second observtion = 9](https://tex.z-dn.net/?f=+%26lt%3Bu%26gt%3B+second+observtion+%3D+9)
▪![<u> third observation = 11 <u> third observation = 11](https://tex.z-dn.net/?f=+%26lt%3Bu%26gt%3B+third+observation+%3D+11)
:)
we know that,
▪
▪
▪
▪
▪
▪
so,
▪
▪
▪
:)
Similar questions